Penerapan Line of Sight dan Finit State Machine pada Game Platformer “RUN!” - Andi Yusika Rangan; Hendy (Digital Transformation Technology, 2023)
At this time, games have expanded their functions beyond mere entertainment facilities; some are used as a means of learning, business land, and even as a sport by professionals. "RUN" is a gender platformer game. In this game, the player controls the main character, who can walk, jump, run, and climb to avoid non-player characters or enemies, as well as pick up items, avoid obstacles, and implement finite state machines and line of sight methods for enemy characters or non-player characters. Application development is a multimedia development method consisting of concept, design, material collection, assembly, testing, and distribution. At the concept stage, what is done is to determine the target user, general specifications, and basic design rules. At the design stage, designing related to game structure includes using case diagrams, activity diagrams, sequence diagrams, and flowcharts. At the material collection stage, images and supporting audio are also needed to make games. At the assembly stage, game-making is carried out based on the design that has been made and the materials that have been collected. Testing is carried out using usability tests, with results showing that 92% of applications can run well. In the final stage, the distribution of the game "RUN!" has been packaged into an application that can be played by all people as entertainment for fans of classic platformer games